Association Between Obstructive Sleep Apnea Severity and Endothelial Dysfunction - Seif, Fadi (2013)
The objective of the study is to examine whether increasing OSA severity is associated with worsening endothelial function. The design is a cross-sectional examination of the baseline assessment of a multicenter randomized controlled clinical trial examining the effects of oxygen, CPAP therapy, or lifestyle modifications on cardiovascular biomarkers. Participants were recruited from cardiology clinics at four sites. Participants with an Apnea Hypopnea Index (AHI) of 15 to 50 and known cardio/cerebrovascular disease (CVD) or CVD risk factors were included. OSA severity indices (oxygen desaturation index [ODI], AHI, and percent sleep time below 90% oxygen saturation [TST<90]) and a measure of endothelium mediated vasodilatation (Framingham Reactive Hyperemia Index, F-RHI derived from peripheral arterial tonometry, PAT) were assessed. The sample included 267 individuals with a mean AHI of 25.0 ± 8.5 (SD) and mean F-RHI 0.44 ± 0.38. In adjusted models, the slope of the relationship between ODI and F-RHI differed above and below an ODI of 24.6 (p=0.04), such that above an ODI of 24.6 there was a marginally significant decline in the geometric mean of the PAT ratio by 3% (95% CI: (0%, 5%); p=0.05) while below this point, there was a marginally significant incline in the geometric mean of the PAT ratio by 13% (95% CI: (0%, 27%); p=0.05) per 5-unit increase in ODI. A similar pattern was observed between AHI and F-RHI. No relation was noted with TST<90 and F-RHI. There was evidence of a graded decline in endothelial function in association withn higher levels of intermittent hypoxemia.